Contributions to the Characterization of Chromogenic Dyes in Color Slides - Silva, Joana (2022)
Funding: This research was supported by Fundação para a Ciência e Tecnologia, Ministério da Ciência, Tecnologia e Ensino Superior (FCT/MCTES), Portugal, through doctoral program CORES-PD/00253/2012, PhD grant SFRH/BD/52317/2013, and Associate Laboratory for Green Chemistry-LAQV financed by national funds (UIDB/50006/2020 and UIDP/50006/2020). This work was also funded through RNEM (Portuguese Mass Spectrometry Network) (LISBOA-01-0145-FEDER-022125–IST).